Competition Law Applications And Encountered Problems In Turkey In The Perspective Of Business Concerns And Personal Consumers - Kortunay, Ayhan; Kortunay, Nevin (European Scientific Journal, ESJ, 2016)
In Turkey in the concept of European Union adaptation process, Law No.4054 on the Protection of Competition has came into effect in 1994. Then in 1997 Turkish Competition Autority has been established. Turkish Competition Law is parallel to competition law’s rules of Europen Union Agreement. In this concept the actions that are forbidded and has monetary penalties are like belows: 1. Agreements, Concerted Practices, and Decisions Which are Restricted Competition 2. Abuse of Dominant Position 3. Merger and Acquisitions That Are Causing Dominant Position or Strengthening of Dominant Position In Turkish Competition Law administrative monetory penalties are being applied to the actions which are lessening competition. These penalities can be up to 10% of the firm’s revenue according to the action’s importance. In this study a general overview will be made for Turkish Competition Law and sample cases of Turkish Competition Authority will be considered. These cases will be analysed in the perspective of business concerns and personal consumers. In the end problems and solution offerings will be discussed.